(untitled) (Al-Qamar, 2023)
Holi is a Hindu religious festival, which started from the subcontinent, which is mostly celebrated at the national level in India and Nepal. There are many mythological traditions associated with the festival of Holi. Among them, the most famous story is considered to be that of prahlad. It is not permissible for Muslims to participate in the religious festivals of non-Muslims or to celebrate any of their religious festivals. It is strictly forbidden, but in some cases a person becomes an infidel and is included from the circle of Islam. Hazrat Allama Mufti Muhammad Sharif-ul-Haq writes that congratulating Holi etc is strictly prohibited rather it is Manjar-ul-Kufr. Those Muslims who do this must repent, renew their faith and marry.